Access to healthcare for undocumented migrants with communicable diseases in Germany: a quantitative study - Mylius, Maren; Frewer, Andreas (European Journal of Public Health, 2015)
Migrants without residence permits are de facto excluded from access to healthcare in Germany. There is one exception in relevant legislation: in the case of sexually transmitted infections and tuberculosis, the legislator has instructed the local Public Health Authorities to offer free and anonymous counseling, testing and, if necessary, treatment in case of apparent need. Furthermore, recommended vaccinations may be carried out free of charge. This study intends to comprehensively capture the services for undocumented migrants at Public Health Authorities in Germany.An e-mail survey of all Local Public Health Authorities (n = 384) in Germany was carried out between January and March 2011 using a standardized questionnaire.One hundred thirty-nine of 384 targeted local Health Authorities completed the questionnaire (36.2%), of which approximately a quarter (n = 34) reported interaction with 'illegal' immigrants. Twenty-give authorities (18.4%) gave the indication to carry out treatment. This outpatient treatment option is mostly limited to patients afflicted with sexually transmitted infections with the distinct exception of human immunodeficiency virus/acquired immune deficiency syndrome.The study highlights the gap between legislation and the reality of restricted access to medical services for undocumented migrants in Germany. It underlines the need of increased financial and human resources in Public Health Authorities and, overall, the simplification of national legislation to assure the right to healthcare.
EVALuna2:5666

Health care for undocumented migrants–a quantitative study on the role of local health authorities in Germany - Mylius, Maren; Frewer, Andreas (Gesundheitswesen, 2014)
Public welfare on a municipal level for groups with special health risks has been an important topic of public health service for more than a century. This notion has been taken up by the German "Protection against Infection Act" (IfSG) in § 19 IfSG. Local health service authorities may provide out-patient treatment in addition to counselling and diagnosis for patients with sexually transmitted infections and tuberculosis, which is covered by public resources in cases of apparent need. Due to altered legislation and increased global mobility, this may become important for migrants without access to regular health care.Aims of this study were recording, counselling, diagnosis and out-patient treatment of migrants without legal residence status under the German Protection against Infection Act in the public health care system.An electronic mail survey of all local health authorities (n=384) by means of a standardised questionnaire was undertaken. Data were analysed using descriptive statistics. In the annex of the questionnaire the participants were asked to describe a case study.139 of 384 local health authorities completed the questionnaire (36.2%) of whom approximately a quarter (24.6%) described contacts to "illegal" migrants. Contacts to migrants without legal residence status are more frequent in cities with more than 100,000 inhabitants than in ismaller cities (p<0.05). 22.6% of all local health authorities make an effort to reach undocumented migrants for counseling and diagnosis. 25 of the local health authorities (18.4%) indicated the capability to provide treatment in accordance with § 19 IfSG. A majority of these local health authorities also have contacts to undocumented migrants (75%). 16 local health authorities (13.3%) provide out-patient treatment for diseases not listed in Protection against Infection Act. 56 authorities (46.7%) refer patients to aid organisations or to resident doctors.Only a small number of local health authorities have contacts to migrants without health insurance. The option-al out-patient treatment is provided by few local health authorities especially in cases of sexual transmitted diseases except for HIV/AIDS. In most cases undocumented migrants are only one group among others. The large number of cases in cities with more than 500,000 inhabitants shows the massive requirements.
EVALuna2:5662
Keywords: access to health care; irregular migrants; HIV; public health service; local health authority; undocumented migrants